Pengaruh Pelatihan Dan Employee Engagement Terhadap Kinerja Karyawan Pada PT Teguhsindo Lestaritama - Retno Karina Sari; Yatimin Yatimin (ITB Ahmad Dahlan Jakarta, 2021)
Human resources are the most important resource in every company because, without the support of appropriate human resources in terms of quantitative, qualitative, strategic, and operational, a company will find it difficult to move forward in running its organization's wheels. This study aims to analyze training and employee engagement on employee performance at PT TeguhsindoLestaritama. The data collection technique is the population or also known as saturated sample. The data analysis method used in this research is multiple linear regression and correlation. Based on the results of this study, the value of multiple linear regression is Y = 12.589 + 0.133 (X1) + 0.593 (X2). These results indicate a positive relationship that training and employee engagement at PT TeguhsindoLestaritamaaffect employee performance.